Bibliography of digital image anti‐forensics and anti‐anti‐forensics techniques. Issue 11 (1st August 2019) - Qureshi, Muhammad Ali; El‐Alfy, El‐Sayed M
Abstract : With the massive increase of online content, widespread of social media, the popularity of smartphones, and rise of security breaches, image forensics has attracted a lot of attention in the past two decades alongside the advancements in digital imaging and processing software. The goal is to be able to verify authenticity, ownership, and copyright of an image and detect changes to the original image. However, more sophisticated image manipulation software tools can use subtle anti‐forensics techniques (AFTs) to complicate and hinder detection. This leads security professionals and digital investigators to develop more robust forensics tools and counter solutions to defeat adversarial anti‐forensics and win the race. This survey study presents a comprehensive systematic overview of various anti‐forensics and anti‐AFTs that are proposed in the literature for digital image forensics. These techniques are thoroughly analysed based on various important characteristics and grouped into broad categories. This study also presents a bibliographic analysis of the‐state‐of‐the‐art publications in various venues. It assists junior researchers in multimedia security and related fields to understand the significance of existing techniques, research trends, and future directions.